The reconstruction of resilience as a social and collective phenomenon: poverty and coping capacity during the economic crisis. Issue 1 (1st January 2018) - Revilla, Juan Carlos; Martín, Paz; de Castro, Carlos
ABSTRACT: Resilience has recently acquired an unusual degree of strength in social research. The article discusses the theoretical and historical background of resilience in the literature in terms of its individual and collective dimensions and argues that, contrary to individualistic conceptions, resilience should be considered a social process linked to social context. It then considers sociological approaches that help to reframe its conceptualisation based on the analysis of data from central Spain within the framework of the RESCuE project, which puts resilience into place in the context of the present economic crisis. Through the analysis of rural and urban case studies the research identifies the importance of the availability of individual and group resources when it comes to the development of resilient strategies in difficult circumstances. Equally, integration into community networks facilitates greater diversity in resilient strategies that can contribute to the recovery and survival of households.